选区激光烧结设备成型缸传动系统及铺粉精度的研究 - 张仟; 党新安; 杨立军 (Jixie chuandong)
Forming cylinder transmission system is the key factor in the accuracy of sprea ding powder of selective laser sintering equipment.According to spreading powder process,the overall plan of forming cylinder transmission system is determined,and the model of the transmission system is established.According to the parameters of spreading powder,the calculation of transmission system dynamic parameters and selection of stepping motor are introduced.In order to meet the accuracy requirements,finally,the analysis of the static positioning error of the drive system is carried out.